An integral equation formulation with global series expansion for resonant wireless power transfer. Issue 5 (4th September 2017) - Bilicz, Sándor; Pávó, József; Gyimóthy, Szabolcs; Badics, Zsolt
Abstract : Purpose: The electromagnetic modeling of inductively coupled, resonant wireless power transfer (WPT) is dealt with. This paper aims to present a numerically efficient simulation method. Design/methodology/approach: Recently, integral equation formulations have been proposed, using piecewise constant basis functions for the series expansion of the current along the coil wire. In the present work, this scheme is improved by introducing global basis functions. Findings: The use of global basis functions provides a stronger numerical stability and a better control over the convergence of the simulation; moreover, the associated computational cost is lower than for the previous schemes. These advantages are demonstrated in numerical examples, with special attention to the achievable efficiency of the power transfer. Practical implications: The method can be efficiently used, e.g., in the optimal design of resonant WPT systems. Originality/value: The presented computation scheme is original in the sense that global series expansion has not been previously applied to the numerical simulation of resonant WPT.